CONSUMPTION OF HYPERLIPIDEMIC DIET AND WATER INTAKE IN ALBINO RATS TREATED WITH ECLIPTA ALBA – ORIGINAL RESEARCH PAPER - SATHEESH NAIK K; RAMANATH B; BHEEMSHETTY S PATIL; SADHU LOKANADHAM (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: A high-fat (HF) diet described as higher calories generating from fat instead of carbohydrate or protein. HF usually diets a typical low-carbohydrate diet. Methods: Thirty adult Albino rats of Wistar strain accurately weighing between 165 and 215 g utilized for the present the study. As per CPCSEA guidelines, the protocol was approved by the institutional animal ethical committee no. BMCH/IAEC/01 Anat/2015 dated June 4, 2015. Animals were maintained and fed with standard rat chow, HF diet, and clean drinking water ad libitum, commercially available and manufactured by the National Institute of Nutrition, Hyderabad. Results: Rate of food consumption increased in rats fed with the HF diet for 8 weeks and decreased significantly in rats treated with Eclipta alba for 1, 2, and 3 weeks progressively compared to control group. Water intake increased in the rats fed with an HF diet (43±2.1) compared to rats fed with a normal diet, decreased significantly in the rats treated with E. alba (31±1.4) compared to the HF diet-fed animals. Conclusion: The rate of food consumption increased in rats fed with the HF diet for 8 weeks and decreased significantly in rats treated with E. alba for 1, 2, and 3 weeks progressively compared to control group. Water intake increased in the rats fed with an HF diet compared to rats fed with a normal diet, decreased significantly in the rats treated with E. alba compared to the HF diet-fed animals